Հին Հայաստանի ապակու մասին - Ժ. Դ. Խաչատրյան (ՀՍՍՀ ԳԱ հրատ․)
The oldest glass-ware samples discovered in Armenia pertain to the second half of the 2 nd millenium. But in Armenia glass had been widespread before our era and in the first centuries A. D. Those cups and flasks both with and without handles, have been of different shapes and color and of a high quality. The best specimens of flasks are those discovered in Upper Artashat and Garny. They are made by blowing and are considered of Sidonian production of the first century A. D. (figs. 1, 2). The flasks discovered in Garny, Gueghadir and the basin of lake Sevan are worth mentioning. These are made in the same way. some have coiled and others bombshaped ornaments.
Keywords: History; Ancient History; D History; N Fine Arts; NKG Glass